CHILDFREE PHENOMENON AMONG URBAN MUSLIMS: A MULTIDISCIPLINARY EXAMINATION OF SCIENCE AND MORALITY - Ma'mun, Sukron; Ahmad Usmani, Sheikh Adnan; Maliki, Ibnu Akbar (AKADEMIKA: Jurnal Pemikiran Islam, 2023)
The concept of childfree is a complex issue influenced by various factors, including economic, cultural, social, and philosophical considerations. A comprehensive understanding of childfree phenomenon necessitates a method that extends beyond religious interpretations and includes other scientific disciplines. Therefore, the integration of morality and science through a multidisciplinary framework is important. In this context, mubadalah method, which corresponded with the integration-interconnection paradigm was a suitable method for unravelling the complexities of childfree in society. Furthermore, childfree was analyzed from the perspective of mubadalah, prioritizing dialogue between science and morality in marriage context. This is a descriptive qualitative study with a literature survey method. The results showed that using semipermeable mubadalah method to analyze the position of childfree in society introduced three new perspectives, namely just, humanist, and perspective rooted in the value of tawhid. These three included some notions, first, the presence of children assumed a central role in marital union and required thoughtful consideration by both partners. Second, childfree was not only about fitrah (innate human disposition), but also included psychological and moral dimensions. Finally, childfree was permissible in the context of Islam from a medical standpoint. These perspectives, derived from medical, moral, and religious interpretations, contributed to a nuanced understanding.